The social media and religion – new challenges (Religious dialogue and cooperation, 2020)
In this paper we analyze the relationship between socialmedia and religion. The subject of the research is to identify thepower and the practical relevance of two spheres which are ofutmost importance for more adequate understanding recent reality.According to Stewart Hoover ‘’ religion and media seem to be evermore connected as we move further into the twenty – first century‘’ (Hoover, 2006:1). Today, social media increasingly become part ofour daily lives; people will find new ways to interact with religionand spirituality. The main goal is to explore the power of socialmedia, and attend to the ways in which these digital technologiesare reconstituting and transforming the religious practices of themodern humans. Increasingly, people are religious or spiritual orinspired by religious texts, but only because they have chosen toplug in and engage with social media. The paper emphasizes therole of social media to represent a new challenge to individuals andinstitutions. This new challenge will create a networked religion, anetworked community; convergent practice; and a multisite reality
Keywords: social media; religion; changes; new challenge; network